2013
DOI: 10.1016/j.joca.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Pain, motor and gait assessment of murine osteoarthritis in a cruciate ligament transection model

Abstract: Objective The major complaint of Osteoarthritis (OA) patients is pain. However, due to the nature of clinical studies and the limitation of animal studies, few studies have linked function impairment and behavioral changes in OA animal models to cartilage loss and histopathology. Our objective was to study surrogate markers of functional impairment in relation to cartilage loss and pathological changes in a post-traumatic mouse model of OA. Method We performed a battery of functional analyses in a mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 40 publications
(43 reference statements)
5
72
0
1
Order By: Relevance
“…In humans, a study conducted with lean and obese individuals indicates similar levels of spontaneous physical activity 37. Furthermore, our result that spontaneous locomotion was independent of injury-induced OA is in agreement with recent findings using cruciate ligament transection OA model in mice 38. It has also been reported that recreational activities do not contribute to OA in normal and overweight individuals 39 40…”
Section: Discussionsupporting
confidence: 93%
“…In humans, a study conducted with lean and obese individuals indicates similar levels of spontaneous physical activity 37. Furthermore, our result that spontaneous locomotion was independent of injury-induced OA is in agreement with recent findings using cruciate ligament transection OA model in mice 38. It has also been reported that recreational activities do not contribute to OA in normal and overweight individuals 39 40…”
Section: Discussionsupporting
confidence: 93%
“…Stride length, step length, step width, and limb duty factor are highly correlated to walking speed; thus, accounting for velocity is absolutely essential 3, 35, 36 . This can be done through statistical models 8 , comparisons to controls 8–10, 25, 37 , or by controlling velocity with treadmill 29, 31, 38–40 . However, it should be noted treadmills can mask subtle spatiotemporal changes by inducing stress, and treadmill measurements vary significantly from open arena measurements 3 .…”
Section: Spatiotemporal Characterizationmentioning
confidence: 99%
“…The discrepancy between these studies may result from the length of time mice were assessed for spontaneous activity. However, when mice receive transection of both anterior and posterior cruciate ligament, they showed decreased rota-rod performance one week post-surgery but maintained the same spontaneous locomotor activity compared to the sham group [ 58 ], which may be related to development of more severe PTA in ACL transected mice than the mice receiving DMM surgery.…”
Section: Mouse Dmm Pta Model and Biomechanical And Neurobehavioral Acmentioning
confidence: 88%